Analisa Pola Perjalanan dan Preferensi Wisata Pada Wisatawan Asal Kota Surabaya Dalam Melakukan Perjalanan Wisata Ke Thailand - Merosa Stephanie (Tourism Retailing+, 2013)
This research is accomplished to reveal the travel patterns and preferences of Surabaya tourist when they travelling to Thailand. Nowadays, Thailand is one of popular destination for Surabaya tourist. During the tour, it will automatically arise a travel patterns and preferences of the individual tourist. Travel patterns and preferences can be vary from one to another tourist.             Analysis techniques used in this research is descriptive with Cross Tabulation and Multiple Correspondence Analysis method. The method aims to determine the relationship between the tourist profile and tourist travel patterns and preferences, supported by correspondence mapping results displayed in the form of image mapping. The results of this research show travel patterns and travel preferences generated varies depending on the tourist's profile.